Seminar Business Model Canvas dan Desain Business Plan Bagi Mahasiswa- Mahasiswi di Kota Medan - Anne Rumondang Malau; Imelda Sitinjak; Libianko Sianturi (Jurnal Visi Pengabdian Kepada Masyarakat, 2022)
The purpose of this community service activity is to provide understanding and motivation on how Medan City students can consider becoming entrepreneurs and become successful by understanding the steps to starting a business through the topic of Business Model Canvas and Business Plan Design. This seminar was held on Saturday, December 11, 2021, online through a Zoom meeting from the Justin Room, HKBP Nommensen University, which was attended by approximately 2oo people. The implementation includes the opening, the MC invites participants to sing, ice breaking, seminars, question and answer sessions, and participant feedback. For the students of this seminar, it is important to understand how to make a business plan by studying the business model canvas and a good business plan design that can help them start a business by making a business plan document. For students, this seminar is a form of training, to train themselves to consider becoming a successful entrepreneur, by being given the task as feedback from this seminar, namely to make a business plan which was collected two weeks after the seminar was held. Although there were some technical obstacles, overall, the seminar participants were very enthusiastic in responding to every interaction with the speakers, they were able to clearly summarize the topics presented and hoped that a further development program would be held, so it can be concluded that the purpose of this service has been achieved.